Reputation: 23268
I am looking for a way to have, I would say synonym keys in the hash.
I want multiple keys to point to the same value, so I can read/write a value through any of these keys.
As example, it should work like that (let say :foo and :bar are synonyms)
hash[:foo] = "foo"
hash[:bar] = "bar"
puts hash[:foo] # => "bar"
Update 1
Let me add couple of details. The main reason why I need these synonyms, because I receive keys from external source, which I can't control, but multiple keys could actually be associated with the same value.
Upvotes: 3
Views: 13349
Reputation: 290
The answer to your original post is:
hash[:foo] = hash[:bar]
and
hash[:foo].__id__ == hash[:bar].__id__it
will hold true as long as the value is a reference value (String, Array ...) .
The answer to your Update 1 could be:
input.reduce({ :k => {}, :v => {} }) { |t, (k, v)|
t[:k][t[:v][v] || k] = v;
t[:v][v] = k;
t
}[:k]
where «input» is an abstract enumerator (or array) of your input data as it comes [key, value]+, «:k» your result, and «:v» an inverted hash that serves the purpose of finding a key if its value is already present.
Upvotes: 1
Reputation: 84343
Depending on how you want to access your data, you can make either the keys or the values synonyms by making them an array. Either way, you'll need to do more work to parse the synonyms than the definitional word they share.
For example, you could use the keys as the definition for your synonyms.
# Create your synonyms.
hash = {}
hash['foo'] = %w[foo bar]
hash
# => {"foo"=>["foo", "bar"]}
# Update the "definition" of your synonyms.
hash['baz'] = hash.delete('foo')
hash
# => {"baz"=>["foo", "bar"]}
You could also invert this structure and make your keys arrays of synonyms instead. For example:
hash = {["foo", "bar"]=>"foo"}
hash[hash.rassoc('foo').first] = 'baz'
=> {["foo", "bar"]=>"baz"}
Upvotes: 9
Reputation: 20408
You could subclass hash and override []
and []=
.
class AliasedHash < Hash
def initialize(*args)
super
@aliases = {}
end
def alias(from,to)
@aliases[from] = to
self
end
def [](key)
super(alias_of(key))
end
def []=(key,value)
super(alias_of(key), value)
end
private
def alias_of(key)
@aliases.fetch(key,key)
end
end
ah = AliasedHash.new.alias(:bar,:foo)
ah[:foo] = 123
ah[:bar] # => 123
ah[:bar] = 456
ah[:foo] # => 456
Upvotes: 5
Reputation: 43815
What you can do is completely possible as long as you assign the same object to both keys.
variable_a = 'a'
hash = {foo: variable_a, bar: variable_a}
puts hash[:foo] #=> 'a'
hash[:bar].succ!
puts hash[:foo] #=> 'b'
This works because hash[:foo]
and hash[:bar]
both refer to the same instance of the letter a
via variable_a
. This however wouldn't work if you used the assignment hash = {foo: 'a', bar: 'a'}
because in that case :foo
and :bar
refer to different instance variables.
Upvotes: 1